2008
DOI: 10.1016/j.cmet.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

RBP4 Disrupts Vitamin A Uptake Homeostasis in a STRA6-Deficient Animal Model for Matthew-Wood Syndrome

Abstract: The cellular uptake of vitamin A from its RBP4-bound circulating form (holo-RBP4) is a homeostatic process that evidently depends on the multidomain membrane protein STRA6. In humans, mutations in STRA6 are associated with Matthew-Wood syndrome, manifested by multisystem developmental malformations. Here we addressed the metabolic basis of this inherited disease. STRA6-dependent transfer of retinol from RBP4 into cultured NIH 3T3 fibroblasts was enhanced by lecithin:retinol acyltransferase (LRAT). The retinol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
236
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(254 citation statements)
references
References 45 publications
16
236
1
1
Order By: Relevance
“…In a STRA6-deficient animal model for Matthew-Wood syndrome, nonspecific RBP4 excess, vitamin A deprivation, or RAR␣ impairment in several tissues is thought to cause multisystem developmental malformations. These fatal consequences were largely alleviated by reducing embryonic RBP4 levels by morpholino oligonucleotide or pharmacological treatments (26). Apparently, the increase of nonfunctional RBP4 in Matthew-Wood syndrome has a role in inducing tissue damage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a STRA6-deficient animal model for Matthew-Wood syndrome, nonspecific RBP4 excess, vitamin A deprivation, or RAR␣ impairment in several tissues is thought to cause multisystem developmental malformations. These fatal consequences were largely alleviated by reducing embryonic RBP4 levels by morpholino oligonucleotide or pharmacological treatments (26). Apparently, the increase of nonfunctional RBP4 in Matthew-Wood syndrome has a role in inducing tissue damage.…”
Section: Discussionmentioning
confidence: 97%
“…2 mg/ml human apo-RBP4 (Sigma) was incubated with 1 mM all-trans-retinoic acid (Sigma) in ethanol containing 10% glycerol (26). Holo-RBP4 was purified by using a Corning Spin-X UF filter tube (Corning).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-mount in situ hybridization was performed according to published protocols (Isken et al, 2008). Bcdo2 was cloned into the vector pCRII-TOPO (Invitrogen, Grand Island, NY), and antisense RNA probes were synthesized as outlined by the manufacturer (Roche Applied Sciences, Indianapolis, IN).…”
Section: Whole-mount In Situ Hybridizationmentioning
confidence: 99%
“…In 2007, Kawaguchi and coworkers could identify Stra6 that acts as a high affinity cell surface receptor for RBP (Kawaguchi, Yu et al 2007), however Stra6 is not expressed in all retinoid metabolizing tissues. Interestingly, cell culture experiments have shown that Stra6-expressing cells, preloaded with retinol, are able to release more retinol into the culture medium than cells without expresson of Stra6 (Isken, Golczak et al 2008), suggesting that Stra6 acts as a bidirectional transporter of retinol. Potentially, Stra6 depending on intracellular retinol/retinoic acid concentration, coordinate retinol uptake /removal, thus avoiding cells to take up toxic amount of retinol.…”
Section: Stra6 (Stimulated By Retinoic Acid Gene 6) (↑)mentioning
confidence: 99%